The archaeology of a fishing community in Hawai‘i as seen within an ethnographically informed context - Loubser, J. H. N. (Southern African Humanities, 2021)
Archaeological data-recovery excavations at Site Complex 50-10-05-4157, near the northwestern corner of the Island of Hawai‘i, showed that by the fourteenth century AD people prepared food at what later became the center of the site complex, presumably during (a) short-term visit(s). The recovery of an increasing amount and variety of marine and terrestrial remains from a sixteenth-century deposit in the same area indicates more intensive use of the locale. The recovery of turtle, shark, coral and urchin abraders, specialized fishing gear, bird and pig bones, and basalt and volcanic glass scrapers from a seventeenth-century altar-like feature conform to male-related activities in the ethnographic record. By the eighteenth century, stonewalled structures had spread to the southern portion of the site complex, some of them most likely being co-residential common houses. Recovery of historic period materials suggests that both the center and southern portions of the site complex were occupied well into the nineteenth century. Compared to the variety of items recovered from structures associated with male-meeting and canoe-maintenance activities, domestic co-residential common houses contained a limited amount and variety of items. The spatial division of the site complex along gender lines is explored in terms of diet, subsistence and manufacturing activities, and religious practices. It is suggested that the standard Hawaiian household complex, or kauhale, comprises spatially separated but paired male and female activity areas. It is also proposed that along the coast a number of kauhales tend to be centered on a bay and communal canoe shed. Agricultural and specialist activity complexes farther inland appear to lack the readily apparent structured nature of a fishing kauhale.